Penerapan Model Project-Based Learning Berbantuan Komik Digital terhadap Kreativitas Siswa dalam Mengapresiasi Cerita Anak Kelas V Sekolah Dasar - Lubis, Wisuda Pramarta; Wulandari, Sri; Sutarini, Sutarini (ARZUSIN, 2026)
Students’ low ability to appreciate children’s stories, particularly in understanding intrinsic elements such as characters, plot, setting, and moral message, as well as their low creativity in expressing story comprehension, constitutes an important problem in Indonesian language learning in elementary schools. This condition is influenced by learning that remains teacher-centered and the lack of use of engaging media. This study aims to improve creativity and the ability to appreciate children’s stories through the implementation of the Project-Based Learning (PjBL) model assisted by digital comic media among Grade V students at SD Negeri 091641 Bandar Tinggi. This study used the Classroom Action Research (CAR) method, which was implemented in two cycles, with each cycle including the stages of planning, implementation, observation, and reflection. The research subjects consisted of 27 students. Data were collected through observation, tests, and documentation using instruments in the form of observation sheets and assessment rubrics for creativity and understanding of the intrinsic elements of stories. The results showed a significant improvement from the pre-cycle to Cycle II. In the pre-cycle, students in the high creativity category reached only 33.33%, whereas those in the low category reached 37.03%. In Cycle I, the high creativity category increased to 68.18%, and in Cycle II it reached 81.48%, with no students in the low category. The ability to understand the intrinsic elements of stories also improved, as reflected in students’ ability to identify characters, understand the plot sequentially, recognize the setting completely, and find the moral message in their own words. The use of digital comics as a learning stimulus helped students understand stories in a visual, engaging, and meaningful way. The conclusion of this study affirms that the implementation of PjBL assisted by digital comics can improve creativity and the ability to appreciate children’s stories. The implications of this study indicate that project-based learning with digital comic media provides space for students to be actively involved, think creatively, collaborate, and express ideas and imagination through real works in the form of scrapbooks and dioramas.